Ray Sharpe, Boorowa, New South Wales, 1974 - Rhodes, Jon, 1947- (1974)
Ray Sharpe wearing an apron standing in the kitchen.
Title from caption list.
Part of: Australia, 1977.
Also available online
Keywords: Sharpe, Ray -- Portraits; Aprons -- New South Wales -- Warren -- Photographs; Kitchens -- New South Wales -- Warren -- Photographs